Mecanismos de defensa del sistema digestivo del cerdo y estrategias de prevención mediadas por inmunidad calostral. Revision de litertura (1997)
ABSTRACT: The digestive tract in one of the places with the highest antigenic challenge in the body in which the immune system should discriminate between infections replicate antigens and soluble and dietary non-replicate one, in order to elicit protective specific immune responses against the former and appropriate not hypersensibility-like reactions against the Second. Thereafter, those efector mechanisms operating at the mucosal level differ with the classic efector mechanisms operating at the systemic evel; i.e. the generation of cytotoxic efector T-cell is not important function in the Gut Associated Lymphoid Tussue (GALT) and the presence of intraepithelial and lamina propria lymphocyte appear to play an important role in the differenciacion of secretory IgA-producing plasma cells. On the other hand, reent knowlegdement achieved in the field of mucosal immunity allowed to desing several experimental protocols for improving the potential immune responses of sucking piglets by previous immunization of the pregnant sow and to test oral vaccination as an interesting approach to elicit more protective immunoprphylactic responses against specific pathogens of the digestive tract. The propose of the pre4sent review is to discuss recent knowledge related to mucosal immunity in pigs and its possible applications in pig industry.